Training, Soft Skills and Productivity: Evidence from a Field Experiment - Maria Prada; Graciana Rucci; Sergio Urzua (Institute of Labor Economics (IZA), 2019)
This paper examines a training intervention aimed at boosting leadership and communication skills among employees of a large Latin American retailer. The identification exploits an experimental design in the context of a difference-in-difference strategy. Using longitudinal information obtained from the firm and two skills surveys, we document large positive effects of the training on store- and individual- level productivity. The intervention was more effective in boosting leadership than communication skills. Spillovers from trained managers to untrained sales representatives also contribute to the main effects. Our findings confirm the possibility of increasing productivity through training targeting critical soft-skills.
Keywords: C93; J24; M53; O15; 330; socio-emotional skills; training; productivity; experiments with firms